Cognitive and Affective Analysis in Water Education and Literacy Through Educational Robotics in Elementary School - Alejandro De la Hoz Serrano; Lina Viviana Melo Niño; Joào Piedade; Florentina Cañada Cañada; Javier Cubero Juánez (Emerging Science Journal, 2025)
The aim of this study was to examine the impact of Educational Robotics on the cognitive and affective development of primary school students in the context of water education and literacy, with a specific focus on learning the water cycle and healthy hydration habits. A quasi-experimental design with a mixed-methods approach was adopted, involving a sample of 158 students (83 girls and 75 boys). The educational intervention consisted of 12 sessions incorporating interactive activities supported by robotics, and data were collected through pre- and post-intervention questionnaires. The findings revealed significant improvements in scientific knowledge, with students reaching an Excellent level in understanding the water cycle and a Sufficient level in hydration-related content. From an affective perspective, positive emotions such as Joy and Enjoyment (81.82%) were predominant, especially in relation to methodological and content aspects, whereas negative emotions were primarily linked to challenges in teamwork and oral communication. The novelty of this study lies in highlighting the value of Educational Robotics not merely as a motivational tool but as a meaningful technological support for learning scientific content. These results emphasize the importance of further research into Educational Robotics potential and the need to address affective barriers to optimize learning outcomes.